Labor dismissal, applicable law and expiration of the action. Reflections on the Ruling of the Social Court of the TSJ of Catalonia of september 9, 2020 - Belintxon Martin, Unai (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Appeal against the judgment of the Social Court which dismissed the claim filed in the first instance for dismissal by considering the exception of lapsing of time filed by the defendant. The Chamber on appeal upholds the first instance decision and errs in classifying as procedural the expiration of the time bar of the action in accordance with the provisions of Articles 3 LEC, 59.3 ET and 103.1 LRJS, inappropriately displacing the application of the Lex Contractus (French Law) in accordance with the provisions of Article 12 of the Rome I Regulation to resolve the aforementioned issue.
Keywords: Applicable Law; European Law; expiry; Rome I Regulation; individual contracts of employment